Enhancing Student Engagement: Effective Strategies for Active Learning in the classroom in Secondary schools - Mduwile, Peter; Dulumoni Goswami (Institute of Educational, Research, and Community Service, 2024)
Student engagement is crucial for academic success, motivation, and overall well-being. Active learning involves students participating in their learning process through activities that require them to think critically, collaborate with their peers, and apply knowledge in real-world scenarios. This paper reviews the current literature on student engagement and active learning, examines the tangible benefits of active learning in the classroom, and provides practical, actionable strategies for teachers to implement. This paper actively explores the issue of enhancing student engagement in secondary schools through the implementation of effective strategies for active learning in the classroom. The research actively focuses on identifying and analysing various methods that have successfully promoted active learning and increased student engagement in the classroom context. Active learning strategies, including project-based learning, technological integration, group projects, and hands-on activities, are included. The paper also discusses the challenges and barriers that may arise when implementing these strategies, such as limited resources, teacher training, and cultural considerations. It provides evidence-based recommendations for overcoming these challenges and promoting student engagement, drawing on insights from the literature review and interviews with educators in Tanzanian secondary schools. This paper offers a thorough grasp of the significance of student participation in secondary education classrooms and helpful advice for educators and school officials on how to improve participation using active learning techniques. By applying these tactics, educators can establish a more vibrant and captivating educational setting promoting student achievement.